Insular cortex involvement in declarative memory deficits in patients with post-traumatic stress disorder - Li Lingjiang; Chen Shulin; Xu Baihua; Liu Jun (BMC Psychiatry, 2009)
Abstract Background Neuroimaging studies have proved that hippocampus relate to the deficient of memory in patients with post-traumatic stress disorder (PTSD). Many studies in healthy subjects also shown that insular cortex (IC) be involved in the declarative memory. This study was designed to investigate whether insular cortex is involved in declarative memory deficits in patients with PTSD. Methods Twelve subjects with PTSD and 12 subjects without PTSD victims underwent functional magnetic resonance imaging and magnetic resonance imaging. All subjects performed encoding and retrieval memory tasks during the fMRI session. Voxel-based morphometry method was used to analyze gray-matter volume, and the Statistical Parametric Mapping (SPM2) was used to analyze activated brain areas when performing tasks. Results Grey matter volume was significantly reduced bilaterally in the insular cortex of PTSD subjects than non-PTSD. PTSD group also had lower level of activation in insular cortex when performing word encoding and retrieval tasks than non-PTSD group. Conclusion The study provides evidence on structural and function abnormalities of the insular cortex in patients with PTSD. Reduced grey-matter volume in insular cortex may be associated with declarative memory deficits in patients with PTSD.